2022
DOI: 10.3390/nu14235195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inulin Intervention on Metabolic Control and Methylation of INS and IRS1 Genes in Patients with Type 2 Diabetes Mellitus

Abstract: Background and Aims: Currently, treatments are being sought to improve the control of type II diabetes mellitus (T2DM), and inulin has been shown to be effective in reducing glucose levels and other metabolic control parameters. These effects on metabolic control may be associated with changes in the epigenetic modulation of genes of the insulin pathway. Therefore, our objective is to determine the effect of agave inulin in metabolic control parameters and in INS and IRS1 genes’ methylation in T2DM patients. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Dietary interventions that can improve gut health or induce protective epigenetics modifications have been studied as cancer prevention strategies in the past decade. As a well-known prebiotic, inulin has been used for treating and preventing digestive problems, weight loss, and constipation because it helps increase the minerals absorption from food, promotes the growth of health-benefiting bacteria, and supports a healthy immune system according to previous studies [33,34]. Our investigation explored the potential mechanisms, gut microbiota regulation, and epigenetics modifications of inulin dietary intervention in BC prevention.…”
Section: Discussionmentioning
confidence: 98%
“…Dietary interventions that can improve gut health or induce protective epigenetics modifications have been studied as cancer prevention strategies in the past decade. As a well-known prebiotic, inulin has been used for treating and preventing digestive problems, weight loss, and constipation because it helps increase the minerals absorption from food, promotes the growth of health-benefiting bacteria, and supports a healthy immune system according to previous studies [33,34]. Our investigation explored the potential mechanisms, gut microbiota regulation, and epigenetics modifications of inulin dietary intervention in BC prevention.…”
Section: Discussionmentioning
confidence: 98%
“…Baseline methylation in the BMAL1 gene negatively correlated with the effect of a 4-month intervention based on an energy-controlled Mediterranean dietary pattern on serum lipids, including the percentage of change in total cholesterol and LDL-c in overweight/obese women [19]. The methylation status of the insulin gene was related to changes in LDL-c after an intervention with inulin agave (10 g/d) over 2 months in patients with type 2 diabetes [20]. Concomitant reductions in the methylation levels of the ADRB3 gene and increases in the HDL-c values were found in overweight/obese women who consumed a diet fortified with folate (191 µg/d) and hazelnut oil (1 capsule/d) for 8 weeks [21].…”
Section: Epigenetic Biomarkers Of Lipid and Lipoprotein Outcomesmentioning
confidence: 96%
“…These disturbances lead to subsequent insulin insufficiency and resistance in the target organs (the liver, muscle, and adipose tissue) [ 41 ], which exhibit inappropriate expression of profibrotic and proapoptotic genes [ 10 , 40 ]. It has been suggested that DNA methylation may be a reversible and dynamic process that requires continuous regulation, and modifications have been described in the methylation of some genes of the insulin pathway, which has provided information on the possible relevant role of epigenetics as a key factor in positive changes in metabolic control parameters in T2DM patients [ 42 , 43 ].…”
Section: Epigenetics In Diabetes Mellitusmentioning
confidence: 99%